2014
DOI: 10.1155/2014/347461
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Photosynthetic Response to High and Low Irradiance ofAeschynanthus longicaulis

Abstract: Aeschynanthus longicaulis plants are understory plants in the forest, adapting to low light conditions in their native habitats. To observe the effects of the high irradiance on growth and physiology, plants were grown under two different light levels, PPFD 650 μmol·m–2 ·s–1 and 150 μmol·m–2 ·s–1 for 6 months. Plants under high irradiance had significantly thicker leaves with smaller leaf area, length, width, and perimeter compared to the plants grown under low irradiance. Under high irradiance, the leaf color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…As expected, and consistent with many previous reports (Griffin et al 2004;Li et al 2014;Mathur et al 2018), savin juniper generally had significantly lower A, g s and NPQ, and significantly higher F v /F m and ΦPSII under 10% light than 100% light, and plants exposed to 50% light had intermediate values . Plants exposed to high light often have lower F v /F m than those exposed to reduced light (Murchie & Lawson 2013).…”
Section: Gas Exchange and Chlorophyll Fluorescence Parameterssupporting
confidence: 92%
“…As expected, and consistent with many previous reports (Griffin et al 2004;Li et al 2014;Mathur et al 2018), savin juniper generally had significantly lower A, g s and NPQ, and significantly higher F v /F m and ΦPSII under 10% light than 100% light, and plants exposed to 50% light had intermediate values . Plants exposed to high light often have lower F v /F m than those exposed to reduced light (Murchie & Lawson 2013).…”
Section: Gas Exchange and Chlorophyll Fluorescence Parameterssupporting
confidence: 92%
“…In this study, LL results in lower AQE, LCP, and Rd. Shading generally induces lower photosynthetic rates and LCP [52]. LCP is the level of light at which photosynthetic CO 2 fixation matches respiratory losses.…”
Section: Discussionmentioning
confidence: 99%
“…moupinensis [ 39 ]. This lower LSP and higher LCP might reveal an adaptive evolutionary trait of plants under higher irradiance [ 40 ]. Based on Maxent modeling, we found that the niche breadth of diploid Fragaria plants was considerably larger than that of tetraploid Fragaria plants and that the tetraploid plants were likely to grow in regions of higher altitude (unpublished data).…”
Section: Discussionmentioning
confidence: 99%